Analysis of adolescents' views on the role of vaccination and limitations in psychosocial functioning during the COVID-19 pandemic - Krzysztof Horoszkiewicz; Bartosz Horoszkiewicz (Kazimierz Wielki University, 2022)
Background. The COVID-19 pandemic has forced entering numerous changes and restrictions on daily psychosocial functioning. The purpose of our research was to explore the views of adolescents aged 14-20 years attending secondary schools on the role of vaccination and the restrictions put in place during the COVID-19 pandemic. Material and methods. The study was conducted with 504 secondary school students in a small town in Poland. Students were aged between 14 and 20 years (M = 16.6, SD = 1.3). The groups were homogeneous in terms of age and gender. 250 males (M = 16.5; SD = 1.3) and 254 females (M = 16.7; SD = 1.4) completed the sheets.   The survey took place between January 7 and 11, 2022. The study used the author's "Pandemic and My Life" survey method. It contained 7 closed-ended questions covering adolescents' attitudes towards COVID-19. Results. More than half of the students have been vaccinated against COVID-19, and they are convinced of the effectiveness of the vaccines. Females were more likely to reveal anxiety before infection. Despite the presence of the COVID-19 virus in many families' homes, concerns about infection were rather small. A great number of the respondents assessed restrictions as "more burdensome than beneficial". Males were more prone to accepting distant education. There was a relationship between students' fear of the COVID-19 infection and the anxiety observed by pupils in their families. Conclusions. The majority of the adolescents surveyed have been vaccinated against COVID-19 and have positive opinions about the effectiveness of the vaccines. There is a strong polarisation of views on some issues. The results obtained can be helpful in building preventive programmes and shaping pupils' health-promoting attitudes.